Thermoelectric properties and stability of Tl-doped SnS - Čermák, Patrik; Hejtmanek, J.; Plecháček, Tomáš; Navrátil, Jiří; Kašparová, Jana; Holy, V; Olmrová Zmrhalová, Zuzana; Jarosova, M.; Beneš, Ludvík; Drašar, Čestmír (Elsevier Science SA, 2019)
Tin sulfide (SnS) is an analog of tin selenide (SnSe) and is a promising thermoelectric material. However, a stable and effective doping of this compound has still not been achieved. According to our observations, this is mainly due to the very low equilibrium solubility of dopants and formation of extraneous phases, which is also an important issue for photovoltaic (PV) applications. Achieving a reasonable (60%) doping efficiency of thallium (Tl) in a cation sublattice of SnSe, we explored the same doping for SnS. Hot-pressed polycrystalline (PC) samples were prepared along with their single-crystalline (SC) counterparts. Samples were examined for extraneous phases by X-ray diffraction (XRD), and energy-dispersive spectroscopy (EDS). Thermal stability was determined by thermogravimetric analysis (TGA). Measurements of the Seebeck and Hall coefficient, and electrical and thermal conductivity were conducted over a temperature range of 80-775 K. The experiments suggested a very low solubility of Tl ( approximate to 0.1%). Slight Tl doping resulted in a substantial improvement of the thermoelectric efficiency (ZT) of SnS and enhanced crystal quality in terms of carrier mobility. We found, however, that attempts to prepare material with a high concentration of Tl or the examination of samples at temperatures above 600 K led to chemical instability. (C) 2019 Elsevier B.V. All rights reserved.
Termoelektrické vlastnosti a stabilita Tl-dopovaného SnS
Keywords: Tin sulfide; Thermoelectric materials; Crystal growth; Doping; Sulfid cínatý; Termoelektrický materiál; Růst krystalu; Dopování